IJBAR NIKAH DALAM PERNIKAHAN ANAK: ANALISIS HUKUM ISLAM DAN PERLINDUNGAN HAK PEREMPUAN - M. Hafil Birbik (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This study examines how the concept of ijbar marriage—the authority of a guardian to marry off a daughter without her consent—is understood within classical Islamic jurisprudence, Indonesian family law, and contemporary social practices, as well as its connection to child marriage. Positioned as a critical intervention in Islamic family law discourse, this research evaluates the compatibility between ijbar and the principles of women’s rights protection. Using a normative qualitative method based on literature review of juristic texts, national regulations, court decisions, and institutional reports, the study finds that classical jurisprudence limits ijbar to clear notions of welfare, yet in practice it is often misinterpreted as justification for forced child marriage. Although Indonesian law has raised the minimum marriage age, legal loopholes remain through the dispensation mechanism, frequently reinforced by misinformed religious narratives. Ethical analysis and maqasid al-sharia perspectives indicate that forced child marriage contradicts the aims of protecting life, dignity, and wellbeing, affirming the necessity of reinterpreting ijbar within contemporary legal and social contexts.